Legalisasi Rasm ‘Uthmani dalam Penulisan al-Qur’an - Zainal Arifin Madzkur (JOURNAL OF QUR'AN AND HADITH STUDIES, 2012)
This article discusses the debates on the use of rasm ‘Uthmani in the writing of the Qur’an. By comparing and analyzing the arguments of three madhhabs, this article argues that the debate has to be ended, since, in principle, the recitation of the Qur’an does not only refer to the text’s writing, but also to its chain of transmission